2013
DOI: 10.1021/la401087j
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Normal Contact Forces between Silica Nanospheres

Abstract: In this work, interaction forces between two silica nanospheres after contact, including the van der Waals (vdW) attraction, Born repulsion, and mechanical contact forces are studied by molecular dynamics (MD) simulations. The effects of interaction path (approach or departure), initial relative velocity, and relative orientations of two nanospheres are first examined. The results show that the interparticle forces are, to a large degree, independent of these variables. Then, emphasis is given to other importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…Based on Eq. (3b) and H i = 30 MPa for the 289 nm NCC, the intrinsic shear resistance force of each NCJ is f i = 140 nN, suggesting capillary [48,49] and/or van der Waals forces [42][43][44][45]. In fact, Gallego-Gómez et al [7] found that a wet SiO 2 NCC is twice as hard as its dry counterpart, implying that the magnitudes of the capillary and van der Waals forces are similar for wet SiO 2 NCCs.…”
Section: Granular Behavior (Regimes I and Ii)mentioning
confidence: 94%
See 1 more Smart Citation
“…Based on Eq. (3b) and H i = 30 MPa for the 289 nm NCC, the intrinsic shear resistance force of each NCJ is f i = 140 nN, suggesting capillary [48,49] and/or van der Waals forces [42][43][44][45]. In fact, Gallego-Gómez et al [7] found that a wet SiO 2 NCC is twice as hard as its dry counterpart, implying that the magnitudes of the capillary and van der Waals forces are similar for wet SiO 2 NCCs.…”
Section: Granular Behavior (Regimes I and Ii)mentioning
confidence: 94%
“…Fig. 4(b) shows that the pristine NCCs exhibit granular behavior: rigid-granule-like NCs are dislodged upon indentation, suggesting weak IPB, likely associated with van der Waals forces and/or capillary interactions [42][43][44][45]. Thus, although each SiO 2 NC is very hard and stiff, the as-assembled NCC is soft and compliant.…”
Section: Effect Of Ald Treatment On the Interparticle Bonding Strengthmentioning
confidence: 99%
“…Details can be found in our previous studies. For brevity, the major simulation procedures are as follows (Sun et al, 2013a(Sun et al, , 2013b:…”
Section: Simulation Conditions and Methodsmentioning
confidence: 99%
“…On the other hand, it is known that the continuum models, developed at the macroscale (Feke et al, 1984;Hamaker, 1937;Johnson, 1985), cannot generally apply to nanoparticles due to the neglect of discrete atomic structure and surface effects (Bishop et al, 2009;Girifalco et al, 2000;Luan and Robbins, 2005). Recently, molecular dynamics (MD) simulation has been developed to calculate the interaction forces between α-quartz silica nanospheres, including the van der Waals (vdW) attraction, Born repulsion and mechanical contact forces during a normal impact (Sun et al, 2013a(Sun et al, , 2013bZeng et al, 2010). Such MD studies can help clarify a series of fundamental issues from atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Besides those asperity models, the adhesive contact, due to vdW forces, between asperities has also been studying using molecular dynamics (MD) methods [8]. MD methods were also used to study the adhesive interactions due to vdW forces of silicon [9], silica [10], and silicon carbide [11] nano-particles. These studies have shown that the JKR and DMT models are valid up to given contact interference distances.…”
Section: Introductionmentioning
confidence: 99%